2001
DOI: 10.1021/np0006364
|View full text |Cite
|
Sign up to set email alerts
|

New Prenylated Bi- and Tricyclic Phloroglucinol Derivatives from Hypericum papuanum

Abstract: Five new prenylated tricyclic and three new bicyclic acylphloroglucinol derivatives have been isolated by bioactivity-guided fractionation of the petroleum ether extract of the dried aerial parts of Hypericum papuanum. The tricyclic compounds (1--5) were named papuaforins A--E. The bicyclic compounds were isolated together with their corresponding tautomers and were named hyperguinones A and B (6/6a,7/7a) and hyperpapuanone (8/8a), respectively. Their structures were elucidated on the basis of extensive 1D and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
45
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…Leach et al [2] reported about the antibacterial activity of a Soxhlet acetone extract of the leaves of H. papuanum (Guttiferae) against the Gram-positive bacterium S. aureus. In our continuing search for biologically active metabolites derived from plants that are employed in the traditional medicine of Papua New Guinea, we have previously isolated 13 acylphloroglucinol derivatives (ialibinones A ± E, papuaforins A ± E, hyperguinones A and B, and hyperpapuanone) from the petroleum-ether extract of this plant [3] [4]. Some of them displayed antibacterial (Bacillus cereus, Staphylococcus epidermidis, and Micrococcus luteus) and cytotoxic activity (KB cells).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Leach et al [2] reported about the antibacterial activity of a Soxhlet acetone extract of the leaves of H. papuanum (Guttiferae) against the Gram-positive bacterium S. aureus. In our continuing search for biologically active metabolites derived from plants that are employed in the traditional medicine of Papua New Guinea, we have previously isolated 13 acylphloroglucinol derivatives (ialibinones A ± E, papuaforins A ± E, hyperguinones A and B, and hyperpapuanone) from the petroleum-ether extract of this plant [3] [4]. Some of them displayed antibacterial (Bacillus cereus, Staphylococcus epidermidis, and Micrococcus luteus) and cytotoxic activity (KB cells).…”
mentioning
confidence: 99%
“…C(1) 65.6 (s b )) 65.6 (s b )) 65.6 (s b )) C (2) 192.8 (s b )) 193.3 (s b )) 193.3 (s b )) C (3) 111.2 (s) 107.4 (s) 107.7, 107.9 (2s b )) C (4) 200.3 (s) 201.7 (s b )) 201.7 (s b )) C (5) 62.5 (s b )) 62.7 (s) 62.9 (s b )) HÀC (6) 53 . system determines the relative configuration at the chirality centres C(1) and C (5). The carbonyl bridge between C(1) and C(5) constrains the substituents at C(1) and C (5) to be cis and, hence, MeÀC (5) is positioned below the plane of the five-membered ring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…838 high antibacterial activity. [6][7][8][9] The Hypericum brasiliense presents three phloroglucinols in its constitution and they are active against bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Phloroglucinol derivatives have been described in the literature as promising substances with high antibacterial activity. [6][7][8][9] The Hypericum brasiliense presents three phloroglucinols in its constitution and they are active against bacteria. 10,11 These phloroglucinols are the japonicin A, the uliginosin B and the isouliginosin B ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%